Variability of fatty acid profiles, oxidative stability and nutritive quality of oil in selected soybean genotypes - Matoša Kočar, Maja (Array, 2020)
The purpose of this study (2010‒12) was to investigate the fatty acid profiles (palmitic – PA, stearic – SA, oleic – OA, linoleic – LA, linolenic – LNA, saturated fatty acids – SFA, monounsaturated fatty acids – MUFA, polyunsaturated fatty acids – PUFA), oxidative stability (MUFA/PUFA, OA/LA), and nutritive quality (LA/LNA) of oil produced by 13 early soybean genotypes created at the Agricultural Institute Osijek, Croatia. The analysis of variance determined significant effect of genotype (G), year (Y), and GxY interaction on all examined traits. The correlation analysis indicated the most important positive correlation existed between the SA and OA, SA and LNA, and LA and LNA, and the most important negative relationship between OA and LA, and OA and LNA. The principal component analysis yielded four significant principal components (PCs) with the eigenvalues >1, which together accounted for 57.84% of the total variability in the data set. The Eigen analysis of the correlation matrix loadings indicated MUFA/PUFA, MUFA, OA/LA, and OA mostly contribute to the PC1 axis and are in a positive correlation with it, while PUFA, LA, and LNA mostly contribute to a negative direction. These results will facilitate the planning of future breeding programs, aimed at adjusting the fatty acid profiles according to the needs of the processing industry and end consumers.